Kinematic analysis and design of a new two-limb parallel Schonflies-motion generator considering isotropic configuration - Wu, Guanglei; Shen, Huiping (Institute of Advanced Engineering and Science, 2022)
This paper presents a new two-limb parallel Schonflies-motion generator, which adopts a pair of alternative spatial modules equivalent to the parallelogram structure. This modular architecture can ensure the enhanced stiffness of the manipulator normal to the motion of the planar parallelogram structure due to the trapezoidal architecture. The preliminary kinematic problems, namely, the mobility, forward/inverse geometry and singularity, are studied as well as the kinematic isotropy. A neutral isotropic configuration of the robot is identified for the structural design of the link lengths.